The SAGE guide to educational leadership and management - English, Fenwick W. (Thousand Oaks, California : SAGE Publications, 2015)
This reference guide provides information on educational management, and insights into challenges facing educational leaders. Emphasis is placed on the skills that effective leaders must develop and refine, including communication, developing teams, coaching and motivating, and managing time and priorities. While being brief, simply written, and a highly practical overview for individuals who are new to this field, this reference guide will combine practice and research, indicate current issues and directions, and choices that need to be made.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 12, 2015).
Keywords: Educational leadership; School management and organization